TFAP2A orchestrates gene regulatory networks and tubular architecture in kidney outer medullary collecting ducts - Leiz, Janna; López-Cayuqueo, Karen I.; Cao, Shuang; Gerhardt, Louisa M. S.; Hinze, Christian; Schmidt-Ott, Kai Martin (JCI insight, 2025)
Mutations in the transcription factor TFAP2A are linked to congenital anomalies of the kidney and urinary tract in humans. While Tfap2a knockout (KO) in mouse collecting ducts leads to tubular epithelial abnormalities, its precise molecular functions in kidney tubules remain unclear. To investigate Tfap2a-dependent gene regulatory networks in the mouse kidney collecting ducts, we employed conditional KO (Hoxb7-Cre; Tfap2afl/fl) models combined with transcriptomics. Histomorphological and physiological assessments of Tfap2a-KO mice revealed progressive postnatal dilation of the outer medullary collecting ducts. Integrating bulk and single-nucleus RNA sequencing with in silico motif mapping in ATAC-seq datasets demonstrated that Tfap2a is highly expressed and active in normal collecting duct principal cells. Comparative transcriptomics between 3-month-old Tfap2a-KO and control mice identified dysregulated genes associated with cell adhesion and WNT signaling, including Alcam and Wnt9b. These changes were confirmed by in situ hybridization. Our findings reveal that Tfap2a regulates medullary collecting duct diameter by orchestrating a transcriptional network involving Wnt9b and Alcam, providing insights into its role in kidney structural integrity.
Gesehen am 05.01.2026